PENGARUH REFORMASI ADMINISTRASI TERHADAP KUALITAS PELAYANAN PUBLIK DALAM PEMERINTAH KECAMATAN KAWANGKOAN KABUPATEN MINAHASA - Mewengkang, Norma (Sam Ratulangi University, 2014)
AbstractRegional autonomy policy encourages Structural, Functional, and cultural changes of the hearts of theRegional Government Administration is expected to improve the capability and effectiveness of LocalGovernment Bureaucracy hearts provide Quality Public Service as expected by the community. Based onBackground Issues The purpose of knowing the factors that influence administrative reform on the quality ofpublic servicesThis research is a survey research and data technique that is descriptive statistical analysis. For informants inthis study is a community of users of purposive services (deliberately) as many as 55 people. Technique ofwriting data through Questionnaire, Interview and Observation.The results of research that is accelerating development in Kawangkoan sub-District Office has not. Itillustrates the attention to the implementation of the Administrative Reformation should be improved. Theresults of the analysis are important. That is, public services can be effectively and efficiently can be realized.Administrative Reform is executed appropriately.Keywords: Administrative Reform, Public Service